Coexisting violence and self‐harm: Dual harm in an early‐stage male prison population. (7th April 2020) - Slade, Karen; Forrester, Andrew; Baguley, Thom
Abstract : Purpose: This study examined the characteristics of men in prison who have a history of both self‐harm and violence (known as dual harm ) and the extent to which demographic and criminogenic factors, in‐prison incidents, and self‐harm method could differentiate men who dual harm. Methods: Official prison sample data were examined for the period April 2010 to November 2017 ( n  = 965). Regression analysis of all custodial incidents, demographic and offending information, and imprisonment experience, was undertaken. Results: Self‐harm was associated with violence in prison, representing a 3.5‐fold risk of violence compared with men who did not self‐harm, after controlling for time in prison, age, and index offence. 60% of men who harmed themselves also engaged in custodial violence, while 32% who were violent also had a self‐harm event. After controlling for age at first incident, 11% of the sample had custodial history of dual harm and they accounted for 56% of all recorded custodial incidents. They had a high probability of property damage and fire setting in prison and spent 40% longer in custody. Men who dual harmed used a greater variety of self‐harm methods, with increased use of lethal methods. Conclusion: Dual harm is prevalent, particularly among those who harm themselves in prison. Men who dual harm contribute excessively to the overall incident burden in prison and demonstrate behavioural variability and risk regarding both violence and self‐harm. The findings challenge the usual distinctive management responses or that self‐harm or violence is solely the responsibility of health or justice, with greater integration required.